Estimation of Isomeric Distributions in Petroleum Fractions - Ha, Zhanyao; Ring, Zbigniew; Liu, Shijie (Energy & fuels, 2005)
This paper proposes a new approach to quantify the compositional distribution of different hydrocarbon isomers in an “isomeric lump” of a crude oil, determined using gas chromatography−mass spectrometry (GC-MS) methods. The concentration distribution of isomers can be determined with good accuracy by minimizing the Gibbs free energy of the mixture containing a set of isomers, subject to the stoichiometric constraint and the measured average boiling point of that isomeric lump. The simulated compositions of the hexane and heptane isomers were compared with the reported analytical results for 18 crude oils. The correspondence between predicted and measured distributions was found to be satisfactory. The experimental distributions of hexane and heptane isomers in those crudes are far from the thermodynamic equilibria, but the introduction of additional experimental information, in the form of the average boiling point of the lump, made it possible to model its isomeric distributions. This finding is important for the derivation of molecular representation for distillates in advanced kinetics modeling of refinery conversion processes.